PEMILIHAN DAERAH PENERIMA BANTUAN LOGISTIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Juniarto, Iis; Widjaja, Ady (STMIK KAPUTAMA, 2021)
Deputy for Logistics and Equipment is a unit that handles requests for logistical assistance as well as equipment in areas that need assistance related to the disaster. Providing Logistical Assistance so far there are still some obstacles including the assessment of the assessment of the eligibility assessment team of the recipient area which is subjective, namely the assessment based on the factor of proximity to the assessment team or from the leader. So those areas that really deserve logistical assistance become unable to get help. The solution to the problem is to use a Simple Additive Weighting (SAW) algorithm that is applied to a decision support system. The results of the study in the form of a decision support system and the results of the system showed the receiving area of aid is Aceh which was selected with a value of 81.17.